Pulling the heartstrings, arguing the case: a narrative response to the issue of moral agency in moral distress. Issue 12 (3rd September 2010) - Walsh, Aileen
Abstract : In this paper it is argued that moral distress is an emotional response to an ethical dilemma, and that to date, the literature has largely failed to address the fundamental questions that need to be answered in response to this emotional response. Firstly, does moral distress accurately identify a wrong being done to patients? Secondly, if it does, can nurses carry out this 'wrong doing', but not be responsible for the consequences of their actions? A narrative that reflects the emotional nature of moral distress is presented, with the aim of providing some answers to these questions.